Music two-point-zero: music, technology and digital independence. Issue 2 (26th November 2008) - Draper, Paul
Internet technologies have enabled a participatory culture which is transforming value systems and opening new pathways for autonomous creativity and innovation. In this web 2.0 phenomenon, social networks continue to define the information society and, in turn, redefine music career opportunities quite differently from traditional preconceptions. In parallel, higher education ideology is consumed by a preoccupation with branding, where universities control websites as information delivery tools, while classroom timetables and e-learning systems systematize pedagogical models which limit students' professional potential. This paper examines this disconnect and frames a praxis intervention project to address the need for dynamic ontologies that can be maintained in a training environment reminiscent of social networking. The project details the outcomes of a longitudinal action research project and makes the case for music 2.0 education, that is, for independent musical craft and technological expertise set in authentic learning contexts.